Analisis Semiotik Charles S. Pierce dalam Drama Drama Mangir Karya Pramoedya Ananta Toer - Humokor, Hikma Nurcahyani; Daud, Rolan K.; Sahari, Sella; Jannah, Firdha Fadhilatul; Kadir, Herson (Jurnal Bahasa, Sastra, dan Budaya, 2024)
This research aims to determine the results of the analysis of Pramoedya Ananta Toer's "Drama Mangir" using Charles Sanders Peirce's Semiotic Theory. This research uses a descriptive method. The source of research data comes from the book "Drama Mangir" by Pramoedya Ananta. The data for this research are signs in accordance with Charles Sanders Peirce's semiotic perspective in the form of iconic signs, indexical signs, symbolic signs found in excerpts from the dialogue "Drama Mangir" by Pramoedya Ananta. This data collection technique is carried out in two ways, namely reading and recording techniques. The data analysis technique is carried out through five stages, namely, (1) classifying data, (2) describing data, (3) analyzing data, (4) interpreting data, and (5) drawing temporary conclusions. The research results that have been described show that the results of the analysis of Pramoedya Ananta Toer's "Drama Mangir" using Charles Sanders Peirce's Semiotic Theory, there are 3 iconic signs that deepen the characterization and relationships between characters,and provide deep symbolic meaning in the story narrative. followed by 3 indexical signs that help form a deep understanding of the characters, their interactions, and the social context in the story, enriching the narrative with concrete and significant details, and 3 symbolic signs that provide a deep understanding of the dynamics of relationships between characters, as well as deepening the narrative by adding layers deep emotional meaning.